Implementation of Islamic Boarding School Socio-Cultural Management-Based Curriculum in Developing of Islamic Educational Institutions Quality - Chusnul Chotimah; Nur Isroatul Khusna; Saiful Amin; Catur Palupi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2022)
The design and implementation of the educational curriculum must be adapted to the socio-cultural conditions of an educational institution. Therefore, in implementing the curriculum, it is better to use appropriate socio-cultural management so that quality development goes well even though it is in educational institutions that have a strong religious system or known as pesantren. The purpose of this research is to know the planning, implementation and evaluation of curriculum based on socio-cultural management in the area of pesantren-based social institutions. This research is a qualitative with the type of case study. Sources of data used are primary and secondary. Data collection techniques in the form of observation and interviews. Data analysis used qualitative data analysis according to Miles and Huberman. The result of this research is that curriculum planning carried out by MTs Nurul Iman Garum is carried out with a process towards a better direction in terms of learning and institutions. In addition, the implementation of the curriculum includes checking teacher readiness, the learning process is supervised by the head of the madrasa, there is an instillation of Islamic values in the learning process, implementing the ubudiyah program, the tahfidz program or additional tutoring. For the evaluation carried out by the MTs Nurul Iman Garum institution, namely; there are two evaluations to measure students' abilities, namely summative and formative evaluations.